Urology instrumentation a comprehensive guide - Sabnis, Ravindra B.; Patwardhan, Sujata K.; Ganpule, Arvind P. (Jaypee, The Health Sciences Publisher, 2016)
Urology Instrumentation - A Comprehensive Guide is an illustrated resource which provides guidance on a variety of surgical instruments for urologists and trainees. The book is divided into fourteen chapters, most of which cover the use of a particular piece of equipment, or group of surgical instruments, including common pitfalls. Instruments and accessories covered include the cytoscope, flexible ureteroscope and cystolithotrity instruments. Other chapters cover energy sources in open, laparoscopic and robotic surgery, sterilisation of equipment, and the final chapter focuses on paediatric urology. 180 illustrations and images, the majority in full colour provide visual guidance. Urology Instrumentation - A Comprehensive Guide combines the indications for, optimal use of, and complications associated with each device, making this an ideal resource for all urologists. Key Points Illustrated guide to instruments for urological surgery Chapters cover individual pieces of equipment and groups of instruments Further chapters on energy sources, and paediatric urology 180 illustrations and images